Strategi Komunikasi Politik Kepala Desa dan Badan Permusyarawatan Desa (BPD) Dalam Mencegah Konflik Sosial - Risma Depyana, Muslan, Abdul Sarlan Menungsa (LPPM Universitas Nahdlatul Ulama Sulawesi Tenggara, 2024)
The political communication strategy of the Head of Ulundoro Village and the Village Consultative Body (BPD) in preventing conflict in Ulundoro Village, Aere District, East Kolaka Regency, Southeast Sulawesi Province is by using an approach system to the community, the village government and BPD are active in carrying out their respective duties and responsibilities, not prioritizing personal interests and using social media as a means of disseminating information about village government policies and BPD supervision so that information can be received by all levels of society in Ulundoro Village, Aere District, East Kolaka Regency.